Stratégies de recherche visuelle et expertise décisionnelle en taekwondo - Milazzo, N.; Rosnet, E.; Fournier, J. (Movement & Sport Sciences - Science & Motricité, 2016)
This study investigates skill-based differences in both visual search strategy and decision-making performances of expert and sub-expert taekwondo fighters in video-based tests. Results revealed that experts were significantly more accurate than their less skilled counterparts to make appropriate decisions. Expert taekwondo fighters used more effective visual search behaviors involving fewer fixations of longer duration on a lesser number of areas of the display. However, analysis of percentage viewing time on different areas showed no difference across groups. In addition, no differences in visual search strategy were observed between successful and unsuccessful decisions. It appears that participants spent more time focusing on the central areas of the opponent`s body and on the regions near to him than on the peripheral areas. Our findings suggest that taekwondo fighters used central and peripheral vision collectively so as to make accurate decision makings.